Взаємодія рослинних олій з робочими контактними поверхнями деталей паливної апаратури дизельних двигунів - Ошовський, В. Я.; Грабовенко, О. І.; Швець, І. А.; Ошовский, В. Я.; Грабовенко, А. И.; Швец, И. А.; Oshovsky, V.; Grabovenko, O.; Shvets, I. (ЦНТУ, 2019)
Виконано аналіз літературних джерел, щодо проблеми руйнування робочих поверхонь основних деталей паливної апаратури дизельних двигунів внаслідок контакту з рідкими паливами альтернативного походження. Проведено металографічне дослідження впливу контакту рослинних палив та дизельного палива на робочі поверхні деталей паливної апаратури дизельних двигунів. Здійснено аналіз впливу альтернативних палив на контактні робочі поверхні деталей диференційованим методом (до та після контакту). Зроблено аналіз отриманих результатів та надані пропозиції щодо подальших робіт по адаптації дизельних двигунів для роботи на рідких альтернативних паливах. Выполнен анализ литературных источников по проблеме разрушения рабочих поверхностей основных деталей топливной аппаратуры дизельных двигателей в результате контакта с жидкими топливами альтернативного происхождения. Проведено металлографические исследования влияния контакта растительных топлив и дизельного топлива на рабочие поверхности деталей топливной аппаратуры дизельных двигателей. Осуществлен анализ влияния альтернативных топлив на рабочие контактные поверхности деталей дифференцированным методом (до и после контакта). Сделан анализ полученных результатов и представлены предложения для дальнейших работ по адаптации дизельных двигателей для работы на жидких альтернативных топливах. A number of published sources point to the problem of the chemical effect of liquid fuels of alternative origin on the metal structure of fuel equipment parts. This in turn creates certain problems in the operation of internal combustion engines using alternative fuels. In this regard, the question of studying the chemical effect of alternative fuels of plant origin on the structure of metals in diesel engine fuel equipment has become urgent. In the course of studying this issue, an analysis of literature on the problem of the destruction of the working surfaces of the main parts of the fuel equipment of diesel engines as a result of contact with liquid fuels of alternative origin was performed. Metallographic studies of the effect of contact between vegetable fuels and diesel fuel on the working surfaces of parts of fuel equipment of diesel engines have been carried out. The analysis of the influence of alternative fuels on the working contact surfaces of parts using a differentiated method (before and after contact) is carried out. The analysis of the results obtained showed the presence of such an effect on the phase components of the material (martensite, carbides and residual austenite) of the parts of the fuel equipment. The greatest influence on the structure of metals was revealed during the contact of the experimental samples with rapeseed and linseed oil. In this regard, it is planned to continue the experiment with expanding the amount of vegetable oils used.
Взаимодействие растительных масел с контактными поверхностями деталей топливной аппаратуры дизельных двигателей
Interaction of Vegetable Oils with the Contact Surfaces of Parts of Diesel Equipment of Diesel Engines
Keywords: мікрошліф; альтернативні палива; паливна апаратура; дизельний двигун; рослинна олія; контактна поверхня; мікроскоп; микрошлиф; альтернативные топлива; топливная аппаратура; дизельный двигатель; растительное масло; контактная поверхность; микроскоп; micro grinder; alternative fuels; fuel equipment; diesel engine; vegetable oil; contact surface; microscope